The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1207/s15327752jpa7101_8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Substance Abuse Subtle Screening Inventory--3 (SASSI--3) in Identifying Substance Dependence Disorders in Clinical Settings

Abstract: This article presents analyses on psychometric properties of a recent revision of the Substance Abuse Subtle Screening Inventory (SASSI-3). Participants were 772 individuals from a range of clinical settings who were independently diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders (3rd ed., rev. [DSM-III-R]; American Psychiatric Association [APA], 1987) or DSM-IV (APA, 1994) criteria regarding the presence or absence of a substance-dependence disorder. A development sample (n = 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 10 publications
1
83
0
Order By: Relevance
“…Assessment of substance dependence was achieved through the use of the Substance Abuse Subtle Screening Inventory (SASSI) (Lazowski, Miller, Boye, & Miller, 1998;Miller & Lazowski, 1999). SASSI was the standard inventory used by the Department of Corrections to determine and forecast treatment needs of correctional populations.…”
Section: Participantsmentioning
confidence: 99%
“…Assessment of substance dependence was achieved through the use of the Substance Abuse Subtle Screening Inventory (SASSI) (Lazowski, Miller, Boye, & Miller, 1998;Miller & Lazowski, 1999). SASSI was the standard inventory used by the Department of Corrections to determine and forecast treatment needs of correctional populations.…”
Section: Participantsmentioning
confidence: 99%
“…The Substance Abuse Subtle Screening Inventory-3 [SASSI-3; Lazowski et al, 1998] contains subscales examining both subtle and obvious aspects of substance abuse, with not all items being face valid to help control for social desirability. In addition, the SASSI-3 includes a defensiveness subscale that aids in identifying those who are not willing to endorse problems and shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Schwartz (1998), in collaboration with the SASSI Institute, found that the SASSI-2 effectively identifies substance abuse and prior criminal involvement. In addition, Lazowski, Miller, Boye, and Miller (1998) studied almost 2,000 participants and found sensitivity and specificity of .97 and .95, respectively.The SASSI-A (Miller, 1990) was designed for use with adolescents. Original validation (Miller, 1990) indicated promising results in the correct classification of substance-dependent adolescents (83%); however, the test was somewhat less successful in correctly classifying adolescents without substance abuse (72%) or those denying substance abuse (69%).…”
mentioning
confidence: 99%
“…On the other hand, Schwartz (1998), in collaboration with the SASSI Institute, found that the SASSI-2 effectively identifies substance abuse and prior criminal involvement. In addition, Lazowski, Miller, Boye, and Miller (1998) studied almost 2,000 participants and found sensitivity and specificity of .97 and .95, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation